Implementation of neural network in game engine to create smart bot and behavior analysis - Shovon, Zamshed Khan; Ahamed, Kaisar; Khan, Tanvir Akram; Hasan, Saad Ziaul (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.